INVESTIGATING THE RELATIONSHIP BETWEEN THE USE OF DOMESTIC RADIO AND THE LEVEL OF SOCIAL TRUST - Farajian, Morteza (2022)
This study studies the relationship between radio usage and social trust. We have considered trust in three types: interpersonal trust, general and institutional trust. The research method used in this research is the survey method that the research data was collected using a questionnaire in the field. Also, 383 samples were selected and operated by systematic cluster sampling. The results show that there is a significant relationship between radio usage and general trust. But there is no significant relationship between radio usage and institutional trust. The results showed that between the use of radio program significantly affects interpersonal trust. Examining the relationship between the use of different types of radio programs with the intermediate variables of the research shows that there is a significant relationship between the use of radio and the intermediate variables of generalism and the feeling of security. The results showed that there is a significant relationship between research mediating variables and the level of social trust in its types of trust. All research mediating variables have a significant relationship with institutional trust. Finally, it can be stated that the use of radio affects the level of social trust by directly affecting social trust and also by indirectly influencing through research interface variables.